The ninth grave : a Fabian Risk novel - Ahnhem, Stefan, 1966- (Minotaur Books, 2017)
"An atmospheric and complicated saga of crimes that criss-cross the narrow strait between Sweden and Denmark...great cop characters...and some imaginatively grisly perps."-- Sunday Times. Would you kill for the one you love? That's the question that international bestseller Stefan Ahnhem's The Ninth Grave: A Fabian Risk Novel seeks to answer in this spine-tingling thriller set six months before the events in Victim Without a Face. On a cold winter evening, the Swedish minister of justice disappears without a trace from the short walk between the house of Parliament and his car. At the same time the wife of a famous Danish TV-star is found brutally murdered in her luxury home north of Copenhagen. Soon more bodies are discovered, all missing different body parts. As criminal investigator Fabian Risk and Danish counterpart Dunja Hougaard race to put the pieces together, they are dragged into a conspiracy worse than anyone could imagine."